Speech Acts of Desiderative Modality of Teachers and Students in Indonesian Language Learning for Class VII of Bumi Shalawat Progressive Middle School - Dwitasari, Arnanda; Werdiningsih, Dyah; Ambarwati, Ari (Journal of Educational Sciences, 2025)
Desiderative speech acts are one of the uses of language used to convey information by speakers to their interlocutors. This study has a primary focus on comprehensively describing the desiderative forms, desiderative functions, and desiderative meanings of speech act modalities that appear in verbal interactions during Indonesian language learning for grade VII at SMP Progresif Bumi Shalawat. In this study a qualitative approach was used. Primary data were collected through authentic audio recordings that captured communication interactions between teachers and students during Indonesian language learning sessions in grade VII. Based on in-depth analysis, there are 10 desiderative modality forms, 6 desiderative functions, and 6 desiderative meanings of speech act modalities present in a rich and varied manner in Indonesian language learning for grade VII at SMP Progresif Bumi Shalawat. These expressions of hope and desire are found both in teacher speech to students and vice versa, demonstrating dynamic communication interactivity.